Pengaruh Efektivitas Komunikasi terhadap Kepuasan Mahasiswa UPR dalam Pelayanan Kesehatan Publik Kota Palangka Raya - Muhammad Hafis Hidayatulah; Candra (LPPM STISIP IMAM BONJOL, 2026)
This study aims to determine the effect of the effectiveness of public health service communication on satisfaction levels among students of Public Administration at the University of Palangka Raya. The quality of public health services is a reflection of good governance, where public satisfaction is the main indicator. Communication between health workers and patients is recognized as a crucial factor that shapes these perceptions and satisfaction levels. This study uses a descriptive quantitative approach with correlation techniques. The local government manages 3 public hospitals and 11 community health centers as well as 2,386 health workers in the city of Palangka Raya. The research sample consisted of 108 students selected through purposive sampling from a population of 173 public administration students enrolled in 2023. The results show that communication effectiveness (X) has a positive and statistically significant effect on satisfaction (Y). However, the coefficient of determination only indicates that communication can explain 13.3% of the variance in service satisfaction. The remaining 86.7% is influenced by other factors not examined in this study, such as structural and operational aspects of service like waiting time, reliability, and physical facilities, as explained in the RATER model. Although communication has been proven to be important, improving overall satisfaction in public health facilities in Palangka Raya requires research and attention to non-communication factors that are more dominant.